Innovation in Public Relations Content of Local Government in Shaping the Image of Regional Heads A Systematic Literature Review in the Digital Era of East Java - Joko Bramono Susilo; Nur Annafi FSM (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
In the digital era, local governments face significant challenges in building a positive public image of regional leaders. The changing public communications landscape driven by technological advancements demands public relations (PR) strategies that are not only informative but also able to engage the emotional and symbolic dimensions of society. The main problem identified is the limited effectiveness of PR content strategies in changing public perceptions. Most content still emphasizes the delivery of factual information, but does not optimally develop narratives, symbols, and interactions that can strengthen the leadership image. This study analyzes this problem using the ADO (Antecedent-Decision-Outcome) approach. Within this framework, PR content innovation is positioned as a prerequisite factor (antecedent), digital communication strategies as the decision (decision), and the formation of the regional leader's image as the final outcome (outcome). The study was conducted using a Systematic Literature Review (SLR) of seven scientific articles that met the inclusion criteria. The analysis is supported by Image Management Theory, Government Communication Theory, and the New Public Governance paradigm, which emphasizes collaboration, transparency, and public participation in governance. Research findings indicate that innovative digital communication strategies—such as the use of social media, visualization of leadership activities, personal narratives, and two-way interactions with citizens—have a significant impact on building and strengthening a positive image of regional leaders. This approach not only increases public trust but also creates more meaningful engagement between leaders and the public. The study's findings confirm that PR plays a strategic role as a key actor in shaping public perceptions of regional leadership in the digital era. The success of image building depends not only on the quality of the message, but also on PR's creativity, consistency, and ability to adapt modern communication technology to meet the dynamics of public information needs and expectations.